Image Photograph - Lafia, Marc (punctum books, 2015)
We no longer live in the society of the spectacle, passively seeing the world. Now we perform our very own spectacle in a society that demands it at every turn. We've become advertisements of ourselves, our own PR agents, continually putting on a performance and measuring it hour by hour. This is no longer the society of the spectacle but the society of performance. All events have become a pretense to create the image, to orchestrate an image of images that is us. We believe the image confers on us a kind of immortality: just as the artist believes her works collected by a major museum will do the same, we believe the network will forever host the archive we build everyday. The image that is us lives in the circulation of the network. Though a file, though virtual and malleable, made out of bits and instantly accessible to anyone who wants to find it around the world, this image that lives only lives on screen, as virtual as it might be, is a material fact. In its impression, its reception, its archivability, its remixability, the electronic image is today's photograph